2013
DOI: 10.4103/0253-7613.111923
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effect of (4-benzylpiperazin-1-yl)(3-methoxyquinoxalin-2-yl)methanone (6g) in experimental mouse models of anxiety

Abstract: Aim:The present study was designed to investigate the anxiolytic activity of 6g, a novel serotonin type-3 receptor (5-HT3) receptor antagonist in experimental mouse models of anxiety.Materials and Methods:The anxiolytic activity of “6g” (1 and 2 mg/kg, intraperitoneally [i.p.]) was evaluated in mice by using a battery of behavioral tests of anxiety such as elevated plus maze (EPM), light-dark (L&D) box, hole board (HB), and open field test (OFT) with diazepam (2 mg/kg, i.p.) as standard anxiolytic. None of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…A compartment entry was considered valid when the animal's all four paws were inside that chamber. The apparatus was thoroughly cleaned with 70% ethanol after each trial [14].…”
Section: Light/dark Aversion Testmentioning
confidence: 99%
See 3 more Smart Citations
“…A compartment entry was considered valid when the animal's all four paws were inside that chamber. The apparatus was thoroughly cleaned with 70% ethanol after each trial [14].…”
Section: Light/dark Aversion Testmentioning
confidence: 99%
“…The ambulation scores (number of square crossed) and rearing number (standing upright on hind legs) were recorded for 5 min period. After each individual test session the floor was thoroughly cleaned with 70% ethanol [14,18].…”
Section: Open Field Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggested that anxiolytic compound have a tendency to reduce the fearful behaviors of rodents in open field. [28] "6n" treatment increased the ambulation scores in OFT indicating the anxiolytic effect of "6n. "…”
Section: Discussionmentioning
confidence: 95%